Model Based Learning and Instruction in Science - Clement, John; Rea-Ramirez, Mary Anne (Models and Modeling in Science Education, 2008)
This book describes new, model based teaching methods for science instruction. It presents research that describes these new methods in a very diverse group of settings: middle school biology, high school physics, and college chemistry classrooms. Mental models in these areas such as understanding the structure of the lungs or cells, molecular structures and reaction mechanisms in chemistry, or causes of current flow in electricity are notoriously difficult for many students to learn. Yet these lie at the core of conceptual understanding in these areas. The studies focus on a variety of teaching strategies such as discrepant questioning, analogies, animations, model competition, and hands on activities. Five different levels of organization for teaching strategies are described, from those operating over months (design of the sequence of units in a curriculum) to those operating over minutes ( teaching tactics for guiding discussion minute by minute).